INTERACTION OF LANGUAGE AND CULTURE IN THE ANALYSIS OF LINGUCULTUROLOGICAL ASPECTS OF PHRASEOLOGIES (Euro-Asia Conferences, 2021)
This article discusses the relationship between language andculture in the analysis of linguocultural aspects of phraseology.Phraseologisms are a spiritual treasure that enriches the language andits content, and they are a linguistic and cultural object that unites theculture of the nation.